2011
DOI: 10.3724/sp.j.1005.2011.01380
|View full text |Cite
|
Sign up to set email alerts
|

Genetic improvement of breeding materials in tropical and sub- tropical maize

Abstract: In the present study, 122 maize local cultivars and adapted exotic germplasm from Thailand were used to develop open pollinate varieties (OPVs) using modified ear-to-row scheme, top-cross or test-cross programmes. Ten new maize OPVs with distinct characters were created based on the precise breeding objectives and directional design. The selection of breeding materials was based upon three factors: elite performance, broad adaptability, and genetic diversity. The synthesizing system provided four features: gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Development of DM resistant varieties becomes a challenge for Isabgol breeders. Characterization of the mechanism underlying DM resistance and the breeding new varieties with resistance and good agronomic traits have been very difficult because resistance to DM is a complex trait and controlled by polygenes [20][21]. Furthermore, current understanding of DM resistance mechanism in Isabgol at the enzyme, gene and regulatory levels is incomplete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of DM resistant varieties becomes a challenge for Isabgol breeders. Characterization of the mechanism underlying DM resistance and the breeding new varieties with resistance and good agronomic traits have been very difficult because resistance to DM is a complex trait and controlled by polygenes [20][21]. Furthermore, current understanding of DM resistance mechanism in Isabgol at the enzyme, gene and regulatory levels is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kotwal et al[34] also found Isabgol transcripts largely aligning to Erythranthe guttata genome. Earlier, Albach et al[49] and Melotto-Passarin et al[50], documented the phylogenetic closeness of the family SI and RI) samples demonstrated the involvement of PP fungal transcripts in compatible interaction with host[16][17][18][19][20][21][22][23][24][25][26][27]. Further analysis PP fungal transcripts may help understand the host pathogen interaction pathways.Gene ontology (GO), is a useful tool to annotate large number of genes and their products and analyze their functions.…”
mentioning
confidence: 99%